Aeronautical chart user's guide - United States. National Aeronautical Charting Office; Federal Aviation Administration (Newcastle, Washington : Aviation Supplies & Academics, 2019)
This 13th edition of the Aeronautical Chart User's Guide is the definitive learning aid, reference document and introduction to the wealth of information provided on FAA charts and in chart navigation publication.
"ASA-CUG-13."
"Effective as of 25 April 2019."
110588
Keywords: Aeronautical charts -- Handbooks, manuals, etc; Handbooks and manuals